Species are lineages of micro-evolutionary interconnected populations: a better delimitation of the evolutionary concept of species - Gustavo Caponi (Principia: An International Journal of Epistemology, 2013)
Species can be defined as a lineage of populations among which was never set up an micro-evolutionary isolation, and what is meant by ‘micro-evolutionary isolation’ is this: two populations are micro-evolutionarily isolated, if and only if, the micro-evolutionary processes affecting one of them (namely: natural selection, genetic drift, sexual selection, mutation and/or migration) cannot reach the other. This is a delimitation of the evolutionary species concept that is compatible and solidary with the conceptual division of labor that some authors have proposed to solve the problem raised by the definition of species.